Factors to drive clinical practice improvement in a Malaysian intensive care unit: Assessment of organisational readiness using a mixed method approach - Soh, Kim; Davidson, Patricia; Leslie, Gavin; DiGiacomo, Michelle; Rolley, John; Soh, K.; Rahman, A. (eContent Management Pty Ltd, 2011)
This study assessed organisational readiness and factors to drive clinical practice improvement for VAP, CRBSI and PU in a Malaysian intensive care unit (ICU). A mixed method study approach was undertaken in a 16-bed ICU in regional Malaysia using an environmental scan, key informant interviews, staff surveys, and patient audit to elucidate factors contributing to planning for clinical practice improvement. Measurements of sustainability of practice and regard for the practice environment were assessed using validated measures. An environmental scan demonstrated high patient occupancy and case load. Nineteen percent of ICU patients developed complications according to validated measures. Survey results indicated that the majority of nurses had a good knowledge of strategies to prevent ICU complications and a positive attitude toward change processes. Engaging executive leadership was identifi ed as crucial in priming the clinical site for practice change. Providing nurses with tools to monitor their clinical practice and empowering them to change practices are important in improving clinical outcomes.